2021
DOI: 10.21203/rs.3.rs-404977/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Antithrombotic Therapy With Non-Vitamin K Antagonist Oral Anticoagulants After Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: Purpose: We performed a meta-analysis to compare the efficacy and safety of antithrombotic therapy with non-vitamin K antagonist oral anticoagulants (NOACs) versus standard care in patients after successful transcatheter aortic valve replacement (TAVR).Methods: A systematic search of PubMed, Cochrane Central Register of Controlled Trials, EMBASE databases and ClinicalTrials.gov Website (through Oct 21, 2020) was performed. Risk ratio (RR) with 95% confidence intervals (CI) for all outcomes were calculated usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A previous meta‐analysis found that DOACs, when compared to vitamin K antagonists (VKA), reduced all‐cause mortality after TAVR in patients with an underlying indication for anticoagulation therapy 13 . However, in patients who undergo TAVR without a concomitant indication for anticoagulation, there is no consensus on whether to administer DOACs or antiplatelet therapy to patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta‐analysis found that DOACs, when compared to vitamin K antagonists (VKA), reduced all‐cause mortality after TAVR in patients with an underlying indication for anticoagulation therapy 13 . However, in patients who undergo TAVR without a concomitant indication for anticoagulation, there is no consensus on whether to administer DOACs or antiplatelet therapy to patients.…”
Section: Discussionmentioning
confidence: 99%